Immunomodulatory and anti-inflammatory properties of immunoglobulin G antibodies - Hematianlarki, Marjan; Nimmerjahn, Falk (Immunological Reviews, 2024)
Antibodies provide an essential layer of protection from infection and reinfection with microbial pathogens. An impaired ability to produce antibodies results in immunodeficiency and necessitates the constant substitution with pooled serum antibodies from healthy donors. Among the five antibody isotypes in humans and mice, immunoglobulin G (IgG) antibodies are the most potent anti-microbial antibody isotype due to their long half-life, their ability to penetrate almost all tissues and due to their ability to trigger a wide variety of effector functions. Of note, individuals suffering from IgG deficiency frequently produce self-reactive antibodies, suggesting that a normal serum IgG level also may contribute to maintaining self-tolerance. Indeed, the substitution of immunodeficient patients with pooled serum IgG fractions from healthy donors, also referred to as intravenous immunoglobulin G (IVIg) therapy, not only protects the patient from infection but also diminishes autoantibody induced pathology, providing more direct evidence that IgG antibodies play an active role in maintaining tolerance during the steady state and during resolution of inflammation. The aim of this review is to discuss different conceptual models that may explain how serum IgG or IVIg can contribute to maintaining a balanced immune response. We will focus on pathways depending on the IgG fragment crystallizable (Fc) as pre-clinical data in various mouse model systems as well as human clinical data have demonstrated that the IgG Fc-domain recapitulates the ability of intact IVIg with respect to its ability to trigger resolution of inflammation. We will further discuss how the findings already have or are in the process of being translated to novel therapeutic approaches to substitute IVIg in treating autoimmune inflammation.
CRIS-Team Scopus Importer:2024-10-04
Keywords: autoimmunity; fc-receptors; immunoglobulin G; intravenous immunoglobulin; resolution of inflammation